"They Want You to Kill Your Inner Queer but Somehow Leave the Human Alive": Delineating the Impacts of Sexual Orientation and Gender Identity and Expression Change Efforts. Issue 5 (13th June 2022) - Goodyear, Trevor; Kinitz, David J.; Dromer, Elisabeth; Gesink, Dionne; Ferlatte, Olivier; Knight, Rod; Salway, Travis
ABSTRACT: Sexual orientation and gender identity and expression change efforts (SOGIECE) aim to suppress the sexual and gender identities of Two-Spirit, lesbian, gay, bisexual, trans, and other queer (2SLGBTQ+) people. Exposure to SOGIECE is associated with significant psychosocial morbidity. Yet, there is a dearth of knowledge specifying the ways in which these psychosocial impacts are produced and experienced. This qualitative interpretive description study aimed to delineate the impacts of SOGIECE. To do so, we thematically analyzed data from in-depth interviews, conducted between January and July 2020, with 22 people with lived experience of SOGIECE. Study participants indicated that feelings of shame and brokenness related to their sexual and gender identities were deeply implicated in and shaped by experiences with SOGIECE. SOGIECE also had socially isolating effects, which had restricted participants' opportunities for meaningful connection with others, including romantic partners and 2SLGBTQ+ communities. Further, SOGIECE had contributed to experiences of profound emotional distress, mental illness (e.g., anxiety, depression), and suicidality. These findings underscore the need for several responsive policy and programmatic interventions, including legislation to prevent SOGIECE, enhanced sexuality- and gender-related educational efforts with the families and support persons of 2SLGBTQ+ people, and targeted mental health screening and supports for SOGIECE survivors.